Cyberbullying And It’s Trauma Among Mobile Legend Gamers In Kendari (Trauma Discourse Analysis) - Martisa, Ela; Rezky Tandi; Ansor Putra; Amiruddin Eso (EDUJ : English Education Journal, 2023)
The purpose of this study is to describe the trauma experienced by Kendari Mobile Legends players due to cyberbullying. The research employs the trauma discourse theory proposed by Indradjadja and Zaumseil. This study's data was collected through interviews with Kendari Mobile Legends players conducted by researchers. In an interview with eight gamers who played the Mobile Legends game, queries pertaining to bullying and its traumatic effects were posed. This investigation employed a qualitative-descriptive approach. In the meantime, the data analysis technique involves presenting, describing, interpreting, and concluding the data. The results revealed that the gamers exhibit trauma symptoms, as indicated by their responses. Among the symptoms of trauma they experienced were a sense of shock and disillusionment as a result of the inappropriate remarks they heard during a game. The other symptoms are dread and concern that they will be subjected to additional cyberbullying. As a sign of their inability to embrace it, gamers frequently reflect on the cyberbullying incident and its origins. Consequently, they become more readily offended, irritable, and whiny. In the meantime, their commonplace feelings of safety and security transform into inner turmoil and hopelessness, revealing their reluctance to exist or live. Based on the results of the analysis, it can be concluded that, as a consequence of cyberbullying, Mobile Legend players in Kendari experienced all symptoms of trauma.